Perencanaan Strategis Pembangunan Berwawasan Budaya Melayu Dalam Mewujudkan Visi Riau 2020 - Muchtar Ahmad (JIP ( Jurnal Industri dan Perkotaan ), 2003)
As human made, philosophically culture is changeable, renewable, dynamic and not final, because it is a response to reality and perfect idea of the culture.